2017
DOI: 10.1038/s41598-017-05781-4
|View full text |Cite
|
Sign up to set email alerts
|

Overstepping the upper refractive index limit to form ultra-narrow photonic nanojets

Abstract: In general, photonic nanojets (PNJs) occur only when the refractive index (Ri) difference between the microparticle and background media is less than 2. The minimum full width at half-maximum (FWHM) of the PNJ is ~130 nm (approximately one-third of the illumination wavelength λ = 400 nm) formed within the evanescent field region. This paper proposes and studies a method to overstep the Ri upper bound and generate ultra-narrow PNJs. Finite element method based numerical investigations and ray-optics theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…D is reduced from 2.2λ 0 to 0.7λ 0 . We notice that both L and D diminish with the reduction of FWHM, as in Ref [16][17][18][19][20][21]. This phenomenon can be compared to the result obtained with a conventional lens for which higher numerical aperture corresponds to a shorter focal length for a constant lens diameter.…”
Section: Ultra-narrow Photonic Nanojetsupporting
confidence: 73%
See 1 more Smart Citation
“…D is reduced from 2.2λ 0 to 0.7λ 0 . We notice that both L and D diminish with the reduction of FWHM, as in Ref [16][17][18][19][20][21]. This phenomenon can be compared to the result obtained with a conventional lens for which higher numerical aperture corresponds to a shorter focal length for a constant lens diameter.…”
Section: Ultra-narrow Photonic Nanojetsupporting
confidence: 73%
“…Yue et al reported a reduction of the FWHM (0.244λ 0 ) using cylindrical metalenses assembled by hexagonally arranged nanofibers [20]. Recently, ultra-narrow PNJs (0.287 λ 0 ) generated by overstepping the upper refractive index limit have been proposed by Gu et al [21]. A review of PNJs has been made by B. S. Luk'yanchuk [22].…”
Section: Introductionmentioning
confidence: 99%
“…2(a) and 2(b), the bright areas in the upper half-cylinder are obviously larger than the bright areas in the case of single dielectric microcylinder. According to classical electromagnetic theory and our previous research, the energy flow diagram denoted by the field lines of time-averaged Poynting vectors can be used to compare and analyze the formation mechanism of PJs and PHs [26,27]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, if the core’s refractive index is smaller than that of the shell ( Figure 2 c), the wavefront’s curvature decreases, generating an elongated nanojet with a lower peak intensity. Numerical simulations indicate that ultra-narrow (width from [ 41 ] to [ 42 , 43 ]) as well as ultra-long (length from ~22 [ 44 ] to 100 [ 45 , 46 ]) nanojets can be generated with core-shell dielectric spheres and cylinders.…”
Section: Practical Considerations For Nanopatterningmentioning
confidence: 99%